Race Treason: The Untold Story of America’s Ban on Polygamy - Ertman, Martha M. (Columbia Journal of Gender and Law, 2010)
Today’s ban on polygamy grew out of nineteenth century Americans’ view that Mormons committed two types of treason. First, antipolygamists charged Mormons with political treason by establishing a separatist theocracy in Utah. Second, they saw a social treason against the nation of White citizens when Mormons adopted a supposedly barbaric marital form, one that was natural for “Asiatic and African” people, but so unnatural for Whites as to produce a new, degenerate species that threatened the project of white supremacy. This Article reveals how both kinds of treason provided the foundation of polygamy law through the discourse of legal, political and medical “experts,” as well as, most vividly, cartoons of the day. This discourse designated the overwhelmingly White Mormons as non-White to justify depriving them of citizenship rights such as voting, holding office, and sitting on juries. Paralleling the Mormon question to miscegenation disputes also raging in the decades after the Civil War, the Article suggests two theoretical perspectives to understand the “blackening” of Mormons. First, postcolonial theorist Edward Said’s concept of Orientalism helps explain how designating Mormons a subject race rendered their subjection inevitable. Second, Sir Henry Maine’s 1864 observation that progressive societies move from status to contract reveals the visceral defense of status embedded in antipolygamy discourse. That defense of status may also have implicated other ways status was giving way to contract, such as wage labor replacing slavery and the partnership theory of marriage beginning to displace coverture. In either case, the Article contends, the racial foundations of American antipolygamy law require us to rethink our own often reflexive condemnation of the practice. It concludes by suggesting three questions to help us frame that inquiry, asking: (1) whether we need to rethink this rarely-enforced ban; (2) whether current antipolygamy law associates polygamy with barbarism, foreignness, and people of color; and (3) whether it is coincidental that the plain language of the Defense of Marriage Act prohibits both polygamy and same-sex marriage.